Innovation and Sustainable Development of Commercial Spaces from the Perspective of Financial Economics - Ma, Jinbo (Asia Pacific Economic and Management Review, 2025)
Under the broad perspective of financial economics, the innovation and sustainable development of commercial spaces have emerged as focal points in the current economic landscape. The innovation of commercial spaces serves as a crucial driver of economic growth. Leveraging the financial support, innovative concepts, and market environment provided by financial economics, it continuously gives rise to new business models, such as e-commerce platforms and shared spaces. For commercial spaces, sustainable development is not only related to ecological environment but also the key to ensuring long-term and stable economic returns. However, in the process of innovation and sustainable development, commercial spaces currently face issues such as capital shortages, homogenization of innovative models, and high environmental protection costs. To achieve the innovation and sustainable development of commercial spaces, it is necessary to integrate financial resources, strengthen financial innovation, promote the diversified development of commercial spaces, enhance environmental awareness, reduce operational energy consumption, and pursue a green development path, so as to achieve a win-win situation in economic and environmental benefits.